2007
DOI: 10.5194/acp-7-2057-2007
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive reactions of aromatic-OH adducts with NO, NO<sub>2</sub> and O<sub>2</sub>: benzene, naphthalene, toluene, m- and p-xylene, hexamethylbenzene, phenol, m-cresol and aniline

Abstract: Abstract. Consecutive reactions of adducts, resulting from OH radicals and aromatics, with the tropospheric scavenger molecules O 2 , NO and NO 2 have been studied for benzene, naphthalene, toluene, m-and p-xylene, hexamethylbenzene, phenol, m-cresol and aniline by observing decays of OH at temperatures where the thermal back-decomposition to OH is faster than 3 s −1 , typically between 300 and 340 K. The experimental technique was resonance fluorescence with flash photolysis of water as source of OH. Biexpone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
132
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(138 citation statements)
references
References 66 publications
5
132
0
1
Order By: Relevance
“…Thus, ipso addition of OH in the gas-phase may be more relevant for more highly-substituted and/or more complex substitutents on aromatics. Koch et al (2007) also pointed out several liquid-phase studies that find evidence of ether bond cleavage. Again, ipso addition of hydroxyl radical is cited as being responsible for ether bond cleavage (removal of an oxy substitutent) and C-C cleavage (removal of a methyl substituent) in some cases.…”
Section: Novel Chemical Pathways For Loss Of Carbon In Methoxyphenol mentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, ipso addition of OH in the gas-phase may be more relevant for more highly-substituted and/or more complex substitutents on aromatics. Koch et al (2007) also pointed out several liquid-phase studies that find evidence of ether bond cleavage. Again, ipso addition of hydroxyl radical is cited as being responsible for ether bond cleavage (removal of an oxy substitutent) and C-C cleavage (removal of a methyl substituent) in some cases.…”
Section: Novel Chemical Pathways For Loss Of Carbon In Methoxyphenol mentioning
confidence: 98%
“…This is the case for alkylbenzenes, in which Noda et al (2009) observed phenol formation from OH-initiated photooxidation of toluene and cresol formation from xylenes. Prior, Koch et al (2007) provided evidence that the ipso addition of OH is relevant for the case of hexamethylbenzene. The extent by which these processes occur in the gas-phase is still unclear, as Aschmann et al (2010) does not observe the dealkylation as in Noda et al (2009).…”
Section: Novel Chemical Pathways For Loss Of Carbon In Methoxyphenol mentioning
confidence: 99%
“…As explained in detail in Ng et al (2007), the alternative reaction of the aromatic-OH adducts with NO 2 is not expected to play a significant role under chamber conditions (Koch et al, 2007). It has been shown that high (>100 ppb) levels of NO x affect the fate of the aromatic-OH-O 2 peroxy radicals Klotz et al, 2002;Volkamer et al, 2002b) (Zhao et al, 2005;Fan and Zhang, 2006), though formation of the phenol product was not considered.…”
Section: Summary Of Soa Yields From Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Atmospheric reaction of these aromatics with the hydroxyl radical (OH) initiates a complex series of gas-phase reactions (Calvert et al, 2002;Koch et al, 2007). As noted above, a crucial factor governing the nature of the gas-phase chemistry and subsequent aerosol formation is the NO x level.…”
Section: Summary Of Soa Yields From Aromatic Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation